(untitled) (Journal of Human Sciences, 2021)
The aim of the research is to identify the role of the College of Education in community service, the sample consisted of (70) faculty members, (31) males and (39) females, and the descriptive approach was used, while the research tool was a ready-made questionnaire prepared by the researcher. Khaled Al-Sahli” and applied to the Saudi environment, and among the most important results of the research are the following: The colleges help to provide the necessary new knowledge and skills in addition to linking the students’ academic learning with practical experiences in the community, and the research recommended the necessity of universities cooperation with each other and with the community. family to support community development.